2015
DOI: 10.1371/journal.pone.0134642
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Training of Alcohol Approach and Drinking Identity Associations in US Undergraduate Drinkers: Null Results from Two Studies

Abstract: There is preliminary evidence that approach avoid training can shift implicit alcohol associations and improve treatment outcomes. We sought to replicate and extend those findings in US undergraduate social drinkers (Study 1) and at-risk drinkers (Study 2). Three adaptations of the approach avoid task (AAT) were tested. The first adaptation – the approach avoid training – was a replication and targeted implicit alcohol approach associations. The remaining two adaptations – the general identity and personalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 56 publications
4
51
4
Order By: Relevance
“…Existing evidence-based interventions for college student hazardous drinking might be strengthened by incorporating strategies designed to change drinking identity. Also, recent advances in cognitive bias modification (see Wiers et al, 2013, but also see Lindgren et al, 2015) and mindfulness training (Ostafin, Bauser, & Myxters, 2012) suggest that IAAs themselves can be changed and that doing so may augment treatment efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence-based interventions for college student hazardous drinking might be strengthened by incorporating strategies designed to change drinking identity. Also, recent advances in cognitive bias modification (see Wiers et al, 2013, but also see Lindgren et al, 2015) and mindfulness training (Ostafin, Bauser, & Myxters, 2012) suggest that IAAs themselves can be changed and that doing so may augment treatment efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these promising results, application of cognitive training in younger populations has proven more difficult [14], for a number of reasons. First, youngsters tend to perceive stronger positive than negative effects of their alcohol use [15], perhaps because positive effects of alcohol tend to occur sooner than the negative effects [16], making those positive associations stronger.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Lindgren et al (2015) found that a training paradigm designed to reduce implicit alcohol approach tendencies in a non-treatment-seeking sample of undergraduate social and risky drinkers did not reduce implicit alcohol associations or drinking outcomes. In a second study, McGeary et al (2014) reported that an online dot-probe based attentional training program did result in significant reductions in alcohol consumption in a group of non-treatment-seeking but heavy-drinking undergraduate students.…”
Section: Discussionmentioning
confidence: 98%
“…In a related literature, a number of studies (e.g., Lindgren et al, 2015; Wiers et al, 2011) have investigated the efficacy of cognitive bias modification (CBM) techniques to modify implicit alcohol-related approach-avoid expectancies (e.g., Palfai and Ostafin, 2003). Research has found that heavy drinkers are faster to use a joystick to “pull” (i.e., approach) computer-presented images of alcohol toward them than they are to “push” (avoid) those same images away (Wiers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation